Comparative cytotoxicity of seven per- and polyfluoroalkyl substances (PFAS) in six human cell lines. (July 2022) - Solan, Megan E.; Senthilkumar, Sanjanaa; Aquino, Grace V.; Bruce, Erica D.; Lavado, Ramon
Abstract: Human exposures to perfluoroalkyl and polyfluoroalkyl substances (PFAS) have been linked to several diseases associated with adverse health outcomes. Animal studies have been conducted, though these may not be sufficient due to the inherent differences in metabolic processes between humans and rodents. Acquiring relevant data on the health effects of short-chain PFAS can be achieved through methods supported by in vitro human cell-based models. Specifically, cytotoxicity assays are the crucial first step to providing meaningful information used for determining safety and providing baseline information for further testing. To this end, we exposed human cell lines representative of six different tissue types, including colon (CaCo-2), liver (HepaRG), kidney (HEK293), brain (HMC-3), lung (MRC-5), and muscle (RMS-13) to five short-chain PFAS and two legacy PFAS. The exposure of the individual PFAS was assessed using a range of concentrations starting from a low concentration (10 −11 M) to a high concentration of (10 −4 M). Our results indicated that CaCo-2 and HEK293 cells were the least sensitive to PFAS exposure, while HMC-3, HepaRG, MRC-5, and RMS-13 demonstrated significant decreases in viability in a relatively narrow range (EC50 ranging from 1 to 70 µM). The most sensitive cell line was the neural HMC-3 for all short- and long-chain PFAS (with EC50 ranging from 1.34 to 2.73 µM). Our data suggest that PFAS do not exert toxicity on all cell types equally, and the cytotoxicity estimates we obtained varied from previously reported values. Overall, this study is novel because it uses human cell lines that have not been widely used to understand human health outcomes associated with PFAS exposure. Graphical Abstract: ga1